2023
DOI: 10.3390/foods12071427
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of a Potential Antifungal Ingredient Using Lactic Acid Bacteria from Dry-Cured Sausages

Abstract: The growing interest in functional foods has fueled the hunt for novel lactic acid bacteria (LAB) found in natural sources such as fermented foods. Thus, the aims of this study were to isolate, identify, characterize, and quantify LAB’s antifungal activity and formulate an ingredient for meat product applications. The overlay method performed a logical initial screening by assessing isolated bacteria’s antifungal activity in vitro. Next, the antifungal activity of the fermented bacteria-free supernatants (BFS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Organic acids have been reported to be useful starting materials in multiple applications which includes food, cosmetic, chemical, pharmaceutical, and beverage industries owing to their various functional properties. Lactic acid, succinic acid and benzoic acid in food have been linked to flavor formation, antimicrobial and antioxidant effects ( Florou-Paneri et al, 2013 ; Majchrzak et al, 2022 ; Punia Bangar et al, 2022 ; Nazareth et al, 2023 ). In UHT milk, B. coagulans CGI314 demonstrated the ability to synthesize the SCFAs; formic acid and acetic acid ( Supplementary Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Organic acids have been reported to be useful starting materials in multiple applications which includes food, cosmetic, chemical, pharmaceutical, and beverage industries owing to their various functional properties. Lactic acid, succinic acid and benzoic acid in food have been linked to flavor formation, antimicrobial and antioxidant effects ( Florou-Paneri et al, 2013 ; Majchrzak et al, 2022 ; Punia Bangar et al, 2022 ; Nazareth et al, 2023 ). In UHT milk, B. coagulans CGI314 demonstrated the ability to synthesize the SCFAs; formic acid and acetic acid ( Supplementary Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…GCC+, as S. xylosus , successfully decreased the OTA content using different strains of P. nordicum (Pn15, Pn92 and Pn856) a in dry-cured ham-based medium, although no effect was detected in sausages inoculated with the same strain of S. xylosus and Pn15 [ 31 , 160 ]. Fermented extracts developed from the fermentation of a meat model system (BFS) by L. plantarum and P. pentosaceus were able to totally eliminate the presence of P. nordicum and P. verrucosum using different concentrations depending on the bacterium and the mold strain tested [ 162 ]. Meftah et al [ 159 ] revealed the ability of the yeasts C. zeylanoides and Rhodotorula mucilaginosa to reduce the OTA concentration produced by P. nordicum and A. westerdijkiae in three matrices (ham, and dry-cured sausages with industrial and traditional processing).…”
Section: Pathogenic and Toxigenic Molds In Ripened Foods And Biocontr...mentioning
confidence: 99%
“…S. xylosus Sx8 was able to control the growth and the AFB1 produced by A. flavus and AFB1 and AF G1 produced by A. parasiticus in a dry-cured ham-based medium at three different temperatures (15, 20 and 25 °C) [ 160 ]. The BFS extract from L. plantarum and P. pentosaceus reduced the growth of A. flavus and A. parasiticus in a meat model system by up to 50% using concentrations between 21 and 43 g L −1 [ 162 ]. D. hansenii combined with the antifungal protein PgAFP and P. acidilactici on slices of dry-cured fermented sausages successfully diminished AFB1 and AFG1 amounts produced by A. parasiticus and the mold counts [ 169 ].…”
Section: Pathogenic and Toxigenic Molds In Ripened Foods And Biocontr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another important property of D. hansenii as a dominant species in dry-fermented sausages, is its antimicrobial capacity [ 24 , 36 ]. Currently, the use of protective cultures in the meat industry is mostly limited to the antifungal capacity of bacteria, such as LAB [ 43 ]. However, yeasts isolated from meat products are also being evaluated for their potential as inhibitors of toxigenic microorganisms with a possible application in the meat industry [ 44 , 45 , 46 , 47 , 48 ].…”
Section: Fungi In Dry-fermented Sausagesmentioning
confidence: 99%